2014
DOI: 10.1002/stem.1626
|View full text |Cite
|
Sign up to set email alerts
|

Megakaryocytes Contribute to the Bone Marrow-Matrix Environment by Expressing Fibronectin, Type IV Collagen, and Laminin

Abstract: Megakaryocytes associate with the bone marrow vasculature where they convert their cytoplasm into proplatelets that protrude through the vascular endothelium into the lumen and release platelets. The extracellular matrix (ECM) microenvironment plays a critical role in regulating these processes. In this work we demonstrate that, among bone marrow ECM components, fibronectin, type IV collagen and laminin are the most abundant around bone marrow sinusoids and constitute a peri-cellular matrix surrounding megakar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
124
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(138 citation statements)
references
References 42 publications
12
124
0
2
Order By: Relevance
“…In contrast to a previous study where collagen I was exclusively found in cortical bone and collagen IV was only associated with vessels (Nilsson et al, 1998), we readily also detected both types in the bone marrow cavity (Fig. 2) in line with a recent study (Malara et al, 2014). The discrepancy between these two recent studies and the study of Nilsson might be attributed to different decalcification methods, as harsh acid treatment can destroy epitopes (Athanasou et al, 1987).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In contrast to a previous study where collagen I was exclusively found in cortical bone and collagen IV was only associated with vessels (Nilsson et al, 1998), we readily also detected both types in the bone marrow cavity (Fig. 2) in line with a recent study (Malara et al, 2014). The discrepancy between these two recent studies and the study of Nilsson might be attributed to different decalcification methods, as harsh acid treatment can destroy epitopes (Athanasou et al, 1987).…”
Section: Discussionsupporting
confidence: 85%
“…It is well known that structural proteins present within the bone marrow cavity and at the vascular niche have an impact on thrombopoiesis (Larson and Watson, 2006). Several in vitro systems have been established to study PPF on plated extracellular matrix (ECM) substrates that include the use of cord-blood-derived CD34+ cells (Balduini et al, 2008;Malara et al, 2011;Sabri et al, 2004) and murine megakaryocytes from bone marrow or fetal liver (Malara et al, 2014). These studies suggest that, although platelet biogenesis is a cell-autonomous process, collagen type I inhibits PPF by preventing premature platelet release in the bone marrow cavity, whereas collagen type IV and laminin support PPF at the sinusoids (Balduini et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in BM and other lymphoid organs indicate that highly plastic ECM networks could play vital roles in steady state as well as pathological hematopoiesis. 61,62 However, not much is known to date on the heterogeneity, biochemical composition, and topology of BM ECM.…”
Section: Org Frommentioning
confidence: 99%
“…Studies in BM and other lymphoid organs indicate that highly plastic ECM networks could play vital roles in steady state as well as pathological hematopoiesis. 61,62 However, not much is known to date on the heterogeneity, biochemical composition, and topology of BM ECM.Spatial organization of hematopoiesis. How the succession of orderly events that leads to continuous hematopoiesis develops within the described tissue microfabric remains poorly understood.…”
mentioning
confidence: 99%
“…CXCL12 is produced by a number of micro-environmental cells, including CXCL12-abundant reticular (CAR) cells [22], nestin+ cells [23], cells of the osteoid lineage [24], arteriolar pericytes [25], and endothelial cells [26]. Once produced, CXCL12 may be bound to matrix components, including fibronectin [27], collagen IV [28], and heparan sulfate [29] expressed within the niche [30,31] potentially refining the activity of this chemokine. Therefore, CXCL12 has the potential to facilitate the retention of HSC in multiple niches within the bone marrow.…”
Section: Introductionmentioning
confidence: 99%